STRATEGIES FOR GROWING PURCHASE INTENTIONS FOR ONLINE SHOPPING THROUGH ANALYSIS OF CONSUMER BEHAVIOR - Nurjaman, Kadar (KOMITMEN: Jurnal Ilmiah Manajemen, 2024)
The purpose of this study is to explore the primary traits that define customer behavior on online shopping platforms in Bandung, Indonesia. The study utilizes the Fundamental Theory-based qualitative investigations to detect and classify variables regarding online purchases based on relevant criteria such as purchase motivation, preferences, consumption patterns, and purchasing patterns. Semi-structured interviews were conducted with customers who had previous experience making purchases online to identify and classify variables regarding internet buying. The study identified three primary categories, namely purchase motivation, experience, and customer behavior. Furthermore, some factors that have a higher impact on consumers' preferences, purchasing decisions, and purchasing habits were discovered. The findings of this study can assist businesses in understanding their customers' behavior and develop effective marketing strategies to increase sales. It can also help policymakers in creating regulations to protect consumers and improve the e-commerce ecosystem in Bandung, Indonesia. This study is among the first to explore the traits that define customer behavior on online shopping platforms in Bandung, Indonesia, and can serve as a reference for future research in the field.